Strengthening the Role of Head Nurses in Managing Quality Improvement (QI) Programs for Pressure Injury Prevention in Hospitals - Hendra Firmansyah; Roro Tutik Sri Hariyati; Lilis Rayatin (Indonesian Journal of Global Health Research, 2025)
Nursing managers face challenges in implementing Quality Improvement (QI) programs for pressure injury prevention in hospitals. Objectives: To identify problems faced by nurse managers in implementing QI programs and to develop problem-solving solutions. Mini-project on improving the quality of care room management and analysis of results and implementation gaps based on literature review. Data collection through interviews, observations, and questionnaires in the internal medicine inpatient ward. Data were analyzed using the 5 Whys technique and fishbone diagram. Problem-solving solutions used the FOCUS PDSA approach. It was found that the direction and control functions of the quality improvement program in efforts to prevent pressure injuries were not optimal. The implementation of solutions in the form of improving pressure injury data management, staff re-education, making mini posters, and evaluating the impact of pressure injuries on costs. The evaluation results showed that all at-risk patients had received preventive interventions and no new cases of pressure injuries were found. Strengthening the direction function of the head of the room through staff re-education, poster installation, and effective monitoring can improve the implementation of the QI program in preventing pressure injuries in hospitals.